New Testament Theology in a Secular World: A Constructivist Work in Philosophical Epistemology and Christian Apologetics - Lampe, Peter (EBL-Schweitzer, 2012)
Contents; Abbreviations; Chapter I Introduction:Indicating the Problem; Chapter II Stages in the History of Thought on the Way toConstructivism; 1 Between Naive Realism and Ontological Idealism; 2 On the Concept of Truth; Chapter III The Brain as a Designer; 1 Neurophysiological Reasons for Constructivism; 2 Does an External Ontic Reality Exist?; 3 The 'Other', the 'Self', and the Freedom of the Will asRealities Constructed by the Brain?; 4 Gaps between Scientific and Everyday-KnowledgeConstructs of Reality; Chapter IV Objectivity as Intersubjectivity:The Interface with Sociology of Knowledge